Schools, Universities and Large-Scale Assessment Responses to COVID-19: The Swedish Example - Marie Wiberg; Per-Erik Lyrén; Anna Lind Pantzare (MDPI AG, 2021)
The aim of this paper is to describe, analyze, and discuss how Swedish schools and the national tests in schools, university teaching and examination, and the college admissions test, Swedish Scholastic Aptitude Test (SweSAT), have been affected by the COVID-19 situation. A further aim is to discuss the challenges in schools, universities and in the admissions test process in Sweden which are due to the COVID-19 situation. Contrary to many other countries, Swedish schools remained open, except for upper secondary school and universities where teaching went online. However, the spring administrations of the national tests and the high-stake college admission test, SweSAT, were cancelled, which had impact on admissions to universities in the fall. By using documentation from the news, school, and university authorities, as well as governmental reports of the events and a student survey, challenges are discussed. The novelty of this study includes a discussion of the events and their upcoming challenges. A discussion of what could be learned and what to expect in the close future is included, as well as conclusions which can be drawn from this situation.